2013
DOI: 10.1128/jcm.00330-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xpert MTB/RIF for Detection of Tuberculosis from Blood Samples of HIV-Infected Adults Confirms Mycobacterium tuberculosis Bacteremia as an Indicator of Poor Prognosis

Abstract: Tuberculosis (TB) remains a leading cause of death among HIV-infected adults, in part because of delayed diagnosis and therefore delayed initiation of treatment. Recently, the Gene-Xpert platform, a rapid, PCR-based diagnostic platform, has been validated for the diagnosis of TB with sputum. We have evaluated the Xpert MTB/RIF assay for the diagnosis of Mycobacterium tuberculosis bacteremia and investigated its impact on clinical outcomes. Consecutive HIV-infected adults with fever and cough presenting to Quee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 19 publications
1
49
1
Order By: Relevance
“…However, many of these prior studies were poorly controlled, and the specificity of the assay used was often uncertain. A recent study showed that the Xpert assay detected TB in blood samples from HIV-positive patients with a sensitivity approximately equal to the sensitivity of blood culture (40). However, we found that only 8.3% of the HIV-negative subjects in our study were TB positive upon blood testing.…”
Section: Figcontrasting
confidence: 55%
“…However, many of these prior studies were poorly controlled, and the specificity of the assay used was often uncertain. A recent study showed that the Xpert assay detected TB in blood samples from HIV-positive patients with a sensitivity approximately equal to the sensitivity of blood culture (40). However, we found that only 8.3% of the HIV-negative subjects in our study were TB positive upon blood testing.…”
Section: Figcontrasting
confidence: 55%
“…The frequency of various factors contributing to test failures is described in Table 2. Literature studies 7,11 suggest that the leading cause of GeneXpert MTB/RIF assay failure results observed in the present study was due to inadequate sample processing and equipment malfunction. Like any other automated laboratory technology, GeneXpert MTB/RIF assay also require a stable electric power supply, and even a short-term interruption of power would result in test failures.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the programmable fluidics of the assay cartridge enabled us to perform double nested-PCR amplification, substantially improving assay sensitivity. The Xpert system has been used successfully to detect Mycobacterium tuberculosis and Staphylococcus aureus directly from clinical blood samples (25,31,32). The current study demonstrates that in the case of F. tularensis bloodstream infection, our approach can diagnose bacteremia several days earlier than conventional PCR or blood culture, with the first cases diagnosed at the time of first symptom development.…”
Section: Discussionmentioning
confidence: 81%